Identification of Historic Artists' Pigments Using Spectral Reflectance and X-Ray Diffraction Properties I. Iron Oxide and Oxy-Hydroxide-Rich Pigments. Issue 1 (February 2016) - Cloutis, Edward; MacKay, Alesha; Norman, Leif; Goltz, Doug
The chemical and mineralogical analyses of art have important cultural, scholarly and historic applications. Investigations can be performed to learn about the history of a particular object, or to investigate techniques for conservation and restoration purposes. In this study, a suite of historic artists' pigments, synthetic samples and end members were analysed to detect specific characteristics that can be applied to their identification and differentiation from other pigments. We combined and compared reflectance spectroscopy (RS; 350–2500 nm) with X-ray diffractometry (XRD) for this purpose. We focused on pigments rich in iron oxides and oxy-hydroxides, specifically ochres, siennas, umbers and "red oxides". It was found that these two techniques are often complementary, and have different strengths and weaknesses. XRD was found to be able to detect a wider range of accessory minerals than RS, and its strength lies in discrimination on the basis of mineral structure. It is less sensitive than RS for detection of poorly crystalline/amorphous phases and fine-grained components. RS is very sensitive to detection and discrimination of different Fe-oxy-hydroxides in the wavelength region below ∼1200 nm. At longer wavelengths (>1200 nm), reflectance spectra can detect the presence of accessory minerals that possess strong absorption features. The analytical strength of RS lies in discrimination on the basis of composition, which is usually linked to specific crystallographic structures. RS and XRD data acquired for powdered mineral pigments can be successfully integrated for the identification of sub-groups within the iron oxy-hydroxide-rich group of pigments, but require further investigation for individual sample discrimination. RS and XRD are also able to verify, disprove or refine identification of the phase(s) that make up these pigments. A major practical advantage of RS over XRD is that RS is a non-destructive, non-contact technique, whereas XRD normally requires removal of a sample from a cultural artefact. One of the main findings is that the reflectance spectra of the pigments present in the mixtures retained their diagnostic absorption features even when mixed with linseed oil. Our results show that RS can be used to discriminate various Fe oxy-hydroxide-rich pigments as well as confirm the organic nature of binders; this has important implications for restoration and conservation of cultural artefacts.